John in Saint Cleron's Manor, Ireland - unknown:::Creator::::::::::::
John Steinbeck and an unnamed man sit at John Huston's Saint Cleran's Manor. Steinbeck considered writing a short novel about Irish rebel Anthony Daly based on history of this estate. Original in safe (color; copy in photo files black and white)